Comparison of inside contact phase and outside contact phase in curved sprinting - Ishimura, K.; Sakurai, S. (ISBS - Conference Proceedings Archive (Konstanz), 2010)
One of differences of running between in straight path and in bent path is the body lean inward. When athletes run in the bent path, athletes are influenced by centrifugal force. Athletes produce the medio-lateral component of ground reaction force (GRF) with inclining the body inward, to balance the centrifugal force. The centripetal force can be estimated by F=mv2 where F is the centripetal force, m is the mass of the body, v is the running velocity, and r is the radius of track. We can see from this equation, the influence of the running velocity on centripetal force is strong. So we can't ignore the centripetal force in sprint race (i.e. 200m dash). The body lean angle increase, as the running velocity increase. Athletes must change the running direction along the bent path. One step of running consist of the flight phase and the contact phase. It is impossible to change running direction during the flight phase. Therefore it is expected to change running direction during the contact phase. It was said the functions of inside and outside legs were asymmetrical (Stoner and Ben-Sira, 1979, Hamill et al, 1987). But there are no study to compare the inside foot contact phase with the outside foot contact phase with in relation to the centripetal force and the body lean angle. The purpose of this study is to compare the inside (left) foot contact phase with the outside (right) foot contact phase with in relation to the centripetal force and the body lean angle. Then we would obtain new knowlege about curved sprinting.